The Influence of Teacher Guidance, Creativity, and Innovation on Students’ Social Studies Project Performance - Supardi Hamid; Elpisah Elpisah; Muhammad Fahreza W; Suarlin Suarlin (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the effect of teacher guidance, teacher creativity, and teacher innovation on students' ability to work on projects (Project Based Learning) in social studies subjects in class VII SMP Negeri 6 Bulukumba. This study used a quantitative approach with total sampling technique, involving 49 students from two classes. Data were collected through questionnaires and analyzed using multiple regression, t-test, and F-test through SPSS 26. The results showed that teacher guidance, teacher creativity, and teacher innovation each had a positive and significant effect on student ability. Simultaneously, the three variables also had a significant influence on students' ability to do social studies projects.